Clavicular Metastasis as an Initial Presentation of Papillary Thyroid Cancer - Russell Fung; Madeline Fasen; Firas Warda; Patrick Natter; Stacey Nedrud; Rui Fernandes; Ahmad Alkhasawneh; Gunjan Y. Gandhi (Case Reports in Endocrinology)
Objective. We present the case of a 44-year-old man with a large neck mass to highlight the unique presentation of papillary thyroid carcinoma (PTC) metastatic to the clavicle. Methods. We reviewed the medical record for a detailed history and physical examination findings. Our radiology colleagues examined the diagnostic imaging studies performed. The pathology team reviewed the neck mass biopsy and the confirmatory surgical pathology after total resection of the mass. Results. A 44-year-old man presented with an enlarging neck mass. Initial X-rays revealed a large soft tissue density mass that extended to the midline of the right clavicle. A neck ultrasound established a 5.4 × 3.6 cm mass with increased vascularity and calcification extending from the thyroid. A CT scan noted the extension of the mass into the adjacent sternoclavicular junction with osteolysis of the middle third of the clavicle and the superior aspect of the sternal body. Fine-needle aspiration revealed a thyroid neoplasm with follicular features and positive immunostaining consistent with thyroid carcinoma. The patient underwent a composite resection of the tumor, including a segmental osteotomy of approximately two-thirds of the medial clavicle. The pathology report confirmed PTC with extrathyroidal extension and clavicle involvement (staged pT4a pN0), with further genomic findings showing positive KRAS mutation. Conclusion. Clavicular metastasis from differentiated thyroid cancer is rare. While the prognosis is generally favorable, various factors, including age greater than 45 years, poor differentiation, follicular thyroid carcinoma, Hurthle cell variant, and extrapulmonary metastasis, have typically been associated with poorer cancer-specific survival.